2013
DOI: 10.1002/art.37936
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Control of Th17 and Th1 Cell Functions by Genetic Variations in Genes Associated With the Interleukin‐23 Signaling Pathway in Spondyloarthritis

Abstract: Objective. Recent genome-wide association studies have revealed numerous genetic associations between specific single-nucleotide polymorphisms (SNPs) and immune-mediated inflammatory diseases. The current challenge is to identify associations of the genetic variants with effector mechanisms implicated in pathogenesis. This study was undertaken to investigate the link between genetic variation at loci associated with spondyloarthritis (SpA) and the effector function of CD4؉ T lymphocyte subsets involved in chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 49 publications
(58 reference statements)
0
23
0
2
Order By: Relevance
“…The protective variant rs11209026 results in a R381Q substitution and functional studies in healthy individuals showed the variant to be a loss of function leading to impaired Th17 effector responses (Di Meglio et al, 2011;Pidasheva et al, 2011;Sarin et al, 2011). In concordance with these data, recent studies showed that genetic variations in genes involved in the IL-23 signalling pathway influence the effector function of Th17 and Th1 cells in patients with AS and in patients with the related skin disease psoriasis (Coffre et al, 2013;Di Meglio et al, 2013). Interestingly, SNPs in IL-23R as well as in IL-23 are also associated with PsA, a distinct phenotypic subset of SpA (Bowes et al, 2011;Filer et al, 2008).…”
Section: Geneticsmentioning
confidence: 76%
“…The protective variant rs11209026 results in a R381Q substitution and functional studies in healthy individuals showed the variant to be a loss of function leading to impaired Th17 effector responses (Di Meglio et al, 2011;Pidasheva et al, 2011;Sarin et al, 2011). In concordance with these data, recent studies showed that genetic variations in genes involved in the IL-23 signalling pathway influence the effector function of Th17 and Th1 cells in patients with AS and in patients with the related skin disease psoriasis (Coffre et al, 2013;Di Meglio et al, 2013). Interestingly, SNPs in IL-23R as well as in IL-23 are also associated with PsA, a distinct phenotypic subset of SpA (Bowes et al, 2011;Filer et al, 2008).…”
Section: Geneticsmentioning
confidence: 76%
“…Such protein-coding changes constitute only a minority of genetic associations with common diseases, perhaps indicative of their relatively pronounced functional effects. In contrast, more subtle effects on gene expression or protein binding, as represented by the IL23R-IL12RB2 association we describe here, are probably more common and may act synergistically 32. Our study highlights the power of conditional analysis to identify the primary genetic disease associations definitively.…”
Section: Discussionmentioning
confidence: 62%
“…In general, polymorphisms influencing gene expression are more likely to be implicated in polygenic diseases like AS. Additive influences arising from numerous SNPs in the IL-23 pathway, which alter the effector functions of Th1-cells and Th17-cells in patients with SpA, have been described32 but the full complexity of the regulation of these cells is only just becoming apparent 33…”
Section: Discussionmentioning
confidence: 99%
“…Цитокины и другие медиаторы, индуцируемые ИЛ17 Выявлено увеличение концентрации широкого спектра «провоспалительных» цитокинов, включая ИЛ17А, ИЛ6, ТФРβ [40][41][42], ИЛ23 [41][42][43][44] в сыворотках пациентов с АС и содержания различных субпопуляций Th17-и Th22-клеток в периферической крови пациентов со СпА [45][46][47][48][49]. Установлено также, что в крови и синови-альной ткани пациентов с АС наблюдается увеличение количества KIR3DL2+ Th17-клеток, взаимодействующих с гомодимером HLA-B27 [50], что способствует «выжива-нию» и усилению синтеза ИЛ17 этими клетками.…”
Section: таблицаunclassified